Modelling the Joint Access Mode and Railway Station Choice - Ghebreegziabiher Debrezion; Eric Pels; Piet Rietveld (Tinbergen Institute, 2007)
This study models the choices of Dutch railway users (aggregated at the 4 digit post code area) for access mode and departure railway stations. For each post code area a set of four access modes: car, public transport, bicycle and walking and a set three departure railway stations are identified. A nested logit model is estimated based on 1440 post code areas using a number of access and rail station features. The access features include distance to the departure station, car ownership level, public transport frequency and travel time by public transport to the departure stations. The station features used in the estimation include rail service quality index and supplementary facilities such as availability of parking space and bicycle standing place. Distance has a negative effect on the utility of departure stations. A steeper effect is observed on the choice of departure stations accessed by the non-motorized modes of walking and bicycle. Availability of parking places and bicycle standing areas have a positive effect on the choice of departure railway stations accessed by car and bicycle respectively. Public transport frequency has a positive whereas public transport travel time has a negative effect on the choice of departure stations accessed by public transport. The rail service quality index of a station has a significant and positive effect on the choice of departure stations accessed by all modes.
Keywords: R2; R4; 330; departure railway station choice; access mode choice; nested logit model; Verkehrsmittelwahl; Bahnhof; Logit-Modell; Niederlande